2019
DOI: 10.1088/1757-899x/529/1/012010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of interphase boundary anisotropy on the three-phase growth dynamics in the β(In) – In2Bi – γ(Sn) ternary-eutectic system

Abstract: We present an experimental investigation on the effects of the interphase energy anisotropy on the formation of three-phase growth microstructures during directional solidification (DS) of the β(In)–In2Bi–γ(Sn) ternary-eutectic system. Standard DS and rotating directional solidification (RDS) experiments were performed using thin alloy samples with real-time observation. We identified two main types of eutectic grains (EGs): (i) quasi-isotropic EGs within which the solidification dynamics do not exhibit any su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 8 publications
0
9
2
Order By: Relevance
“…[32], could be used so that the 2Dto-3D transition could be avoided at larger velocities. Among other prospects, the thin-sample solidification methodology could be also extended to three-phased growth microstructures in Al-based alloys [54,55]. Finally, the present study may provide fundamental hints for a practical endeavor aiming at developing new meth-ods for the control of textures in directionally solidified eutectic materials that present several types of ORs.…”
Section: Discussionmentioning
confidence: 83%
“…[32], could be used so that the 2Dto-3D transition could be avoided at larger velocities. Among other prospects, the thin-sample solidification methodology could be also extended to three-phased growth microstructures in Al-based alloys [54,55]. Finally, the present study may provide fundamental hints for a practical endeavor aiming at developing new meth-ods for the control of textures in directionally solidified eutectic materials that present several types of ORs.…”
Section: Discussionmentioning
confidence: 83%
“…With the development of eutectic solidification theory and research methods, the importance of interfacial energy anisotropy on tilted eutectics is well recognized. [7,[25][26][27][28][29][30][31][32][33][34] From the in-situ directional solidification experiments of transparent alloys, Caroli et al [25] found that the tilted growth of lamellae and symmetry reflection of the solid-liquid interface front profile are broken, induced by interfacial energy anisotropies. Having made further theoretical analysis, they concluded that the anisotropy of solid-solid interface energy attempts to tilt lamellae into the orientation with the lowest α/β interface energy, while the anisotropy of solid-liquid interface energy may modify the pinning angle for α phase and β phase at triple points.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to binary eutectic alloys several experimental studies have been conducted on three-phase eutectic alloys, that include Ag-Al-Cu [16][17][18][19][20][21][22], In-Bi-Sn [23][24][25][26][27][28][29][30], Sn-Ag-Cu [31],…”
Section: Introductionmentioning
confidence: 99%